Shadowed scar tissue: an in-depth literature review of interpersonal hurt in romantic relationships - Dickey, Janet M. (Kansas State University, 2012)
Interpersonal hurt in romantic relationships describes many every day interactions couples have. However, these instances of hurt are difficult to identify, talk about, and react to, making the study of such interactions immensely difficult as well. This in-depth literature review of current scholarly work is compiled in an effort to provide groundwork for understanding what hurt is, how individuals conceptualize the hurt they feel, and the coping strategies used to overcome what some scholars call a communicative and social phenomenon. Further, a discussion of future avenues of research and the implications of an expansion on the current research aims to guide future scholars to better understand what so many scholars are attempting to get a handle on.
Keywords: Interpersonal hurt; Romantic relationships; Coping; Attribution; Communication (0459)